Hubungan Vegetasi Mangrove Terhadap Kelimpahan Makrozoobenthos di Pantai Pangkajene - Ambeng Ambeng; Hazairin Zubair; Putu Oka Ngakan; Adi Tonggiroh (Universitas Hasanuddin, 2020)
Mangrove ecosystem is a habitat of various fauna, especially macrozoobenthos. The changing vegetation of the mangrove ecosystem will influence the abundance of macrozoobenthos. This study was conducted in April-August 2019 and aims to analyze the dominance and density relations of mangrove vegetation against the abundance of Macrozoobenthos on the Pagkajene coast. The research location is conducted on three stations, each station is divided into two sampling areas, and on each sampling area is placed six sampling points. Data collection of mangrove vegetation is used with a multilevel plot method and Macrozoobenthos using a plot 50x50 cm. correlation the dominance and density of mangrove vegetation towards the abundance of macrozoobenthos used linear regression analysis. The results of the study gained that the mangrove vegetation dominancy positively affects to the abundance of macrozoobenthos but insignificant. Meanwhile, the density of mangrove vegetation significantly negatively affects to the abundance of macrozoobenthos.